Unlocking Economic Potential: Leveraging Maqâshid al-Syarî'ah Achievements to Boost Investment in OIC Countries - Hariyani, Happy Febrina; Fuddin, Muhammad Khoirul (Faculty of Economic an Business Wijaya Kusuma Surabaya University, 2023)
The study investigates the factors influencing investment ratings within OIC (Organization of Islamic Cooperation) countries from 2011 to 2015. We employed the Tobit Regression model as our primary analytical tool to achieve this objective. Our data sources encompassed secondary data sets published by reputable organizations such as the World Bank, Transparency International, and UNDP. We utilised purposive sampling, targeting 19 OIC nations for which comprehensive data on the required variables were available. The model featured five independent variables: the Corruption Perception Index, GDP per capita, population growth, life expectancy, and the education index. The sole dependent variable under examination was the investment rating. Our findings unveiled that the Corruption Perception Index and GDP per capita significantly influenced the investment ratings within OIC countries. It implies that perceptions of corruption and economic prosperity played pivotal roles in shaping the investment climate within these nations during the specified period.